Mammalian acetate metabolism - Keane, D (1967)
This work is a study of sense aspects of the metabolism of free acetic acid in non-ruminant mammals. The metabolic significance of acetate is recognized in the ruminant and in certain micro-organisms where large amounts of acetate are utilized. The lack of a sufficiently sensitive method for acetate determination coupled with the low concentrations present in the tissues of non-ruminants has been a major impediment to studies on acetate metabolism in these animals in the past. A method suitable for acetate determination in the tissues of non-ruminants has been developed. The study has been pursued by measurements of acetate in blood and tissues of the rat, and by investigating acetate production in in vitro preparations of rat liver and comparing it with that of ketone bodies. Chapter 1. Introduction. The reasons for undertaking this study are described. the presence of small amounts of acetate in animal tissues and its ready utilization by selective tissues suggest that acetate may have a role as a respiratory fuel analogous to that discussed by Krebs (1961a) for the ketone bodies. The pathways of metabolism of acetate and the acetyl group are briefly outlined; and the possible precursors of free acetate and the likely sites of its formation in the body are described. Chapter 2. Development of a method for the measurement of acetic acid. Many Methods of acetate determination used by earlier workers have been investigated. Microdiffusion, (Serlin and Cotzias, 1955), even with various modifications, has not been found to be sufficiently sensitive for the present purpose; lactate and bicarbonate have been found to cause considerable interference in a micro-distillation method (Bartley, 1953). An attempt was made to obtain an active preparation of acetokinase (E. Coli), but since the Km value of the enzyme is so high (0.3 M acetate, Rose, Grunberg-Manago, Korey and Ochoa, 1954), the amounts of enzyme required to measure low concentrations of acetate would be relatively large, so enzymic assays were not pursued. Finally, a gas chromatographic method (Baumgardt, 1964) has been adapted. This system can take aqueous samples thus cutting out the need for cumbersome extraction procedures. However, the samples must first be purified by steam-distillation (Dr. E.F. Annison, personal communication). Isovalerate is used as a marker. The method is specific for acetic acid. The mean recovery of 1 - 10 μmoles of acetate added to blood, perfusion medium or tissue homogenate is between 93% and 105%, while the individual errors are ± 29% at worst. Amounts of acetate of 0.08 μmole and upwards can be determined. Chapter 3. Acetate in rat blood and its origin. The acetate level in rat blood, collected by cannulation of the aorta , remains at approximately 0.4 mM regardless of dietary alterations (feeding , fasting for 24 or 48 hr., high-roughage diet), but blood from the portal vein which drains i.e. the caecum. contains 4 times as much acetate, and small amounts of other volatile fatty acids, notably propionate. This difference in concentration in the blood from different parts of the body points to (i) an Intestinal origin of acetate, and (ii) uptake of acetate from the blood by the liver and possibly the heart. The caecum contents contain relatively large amounts of volatile fatty acids (approximately 50 μmoles/g.) of which about 50% is acetate. The volatile fatty acid composition is similar to that of sheep rumen contents (Annison, 1954b), although on a smaller scale. The concentration of acetate in caecum contents is only half that in the rumen, and relative to body weight, the rat caecum is only about 1% while the sheep rumen is approximately 10 - 20% (from Annison and Lewis. 1959; Bergman, Reid, Murray, Brockway and Whitelaw. 1965). Oral treatment of the rats with neomycin, an antibiotic, to reduce the bacterial activity of the gut to a minimum, decreases the acetate in the caecum contents to one-fifth and in the portal blood to one-third of their normal concentrations, the acetate in portal blood now being within the range found in aortic blood. It is concluded that acetate in rat blood arises at least partly by bacterial activity in the Intestine. and especially within the caecum. A calculation based on the arterio-portal venous difference for acetate and on an approximation of portal blood flow rate (from Dobson and Jones , 1952) show that the acetate absorbed daily from the intestine, if completely oxidised, could account maximally for 10% of the basal caloric output in the rat , as compared with a corresponding value of 42% in the ruminant (Bergman et al. 1965). Chapter 4. Acetate in the tissues of normal and alloxan-diabetic rats. The tissue levels of acetate are comparable with those found by an enzymic assay (Bergmeyer and Moellering , 1966), and are highest in liver at about 0.4 μmole/g. fr. wt., intermediate in kidney, and lowest in heart muscle which readily utilizes acetate (Wllliamson, 1962). Acute alloxan-diabetes causes the level to rise by 150% in liver and by 50% in kidney, while the concentration in blood and in heart muscle remain unchanged. Fasting (48 hr.) or bran- feeding have no effect on liver acetate level. The factors which generate and dispose of from acetate are discussed , but the control of its level is not sufficiently understood to offer a satisfactory explanation for the altered levels in diabetes. Chapter 5. Acetate and ketone body production by rat liver in vitro. Preliminary experiments have shown that acatate is produced by rat liver slices, at a rate coaparable to that of ketone body formation, and that it is increased by the addition of fatty acids. In the perfused liver much higher rates of production of both acatate and ketone bodies are observed; the maximal endogenous rates are 45 μmole. acetate/g. fr. wt./hr., and 42 μmoles total katone bodies/g. fr. wt./hr. (in the livers of 48 hr. fasted rats). This preparation is adopted for further investigation of the effects of dietary alterations and of the addition of various precursors of the acetyl group (fatty acids, pyruvate and ethanol)> The initial rate of acetate formation is constant, but it starts to decline more rapidly in the livers of fed rats (after 30-60 min.) than in those of 48 hr. fasted rats (after 60-90 min.). Ketogenesis is minimal when donor rats are fed and is markedly and progressively increased when the rats are fasted for 24 and 48 hr. Addition of fatty acids with or without carnitine has no affect on acatate production, but greatly enhances that of katone bodies. It is calculated from net metabolic changes, that 2 mM butyrate is quantitatively converted, and 0.5 mM oleate is 60% converted to ketone bodies. The fate of the remaining oleate has not been determined. It is probably partly converted to CO2 and partly utilized by the biosynthetic reactions of acetyl CoA. Added ethanol and pyruvate are strongly anti-ketogenic, and do not alter acetate formation when the donor rats are fasted. Whan the rats are fed, acetate production is enhanced by 5 mM ethanol (2 perfusions), probably related to the higher activities of liver alcohol and aldehyde dehydrogenases (EC 1.1.1.1., EC 1.2.1.3.) in that state (Büttner, 1965). Such large-scale acetate production by rat liver preparations was not previously observed (Hochheuser, Weiss and Wieland, 1964; Hepp, Prüsse, Weiss and Wieland, 1966a,b). The evidence for the metabolic origin of the acetate appearing in the perfusion medium is summarised, and the likely endogenous precursors of this acetate are discussed. Chapter 6. Additional comments. On the basis of the present findings some possible approaches to the further study of acetate metabolism in the rat are suggested; and a modification to the method of acetate determination is tentatively proposed.